2003
DOI: 10.1074/jbc.m306147200
|View full text |Cite
|
Sign up to set email alerts
|

Structure-based Incorporation of 6-Methyl-8-(2-deoxy-β-ribofuranosyl)isoxanthopteridine into the Human Telomeric Repeat DNA as a Probe for UP1 Binding and Destabilization of G-tetrad Structures

Abstract: Heterogeneous ribonucleoprotein A1 (hnRNP A1) is an abundant nuclear protein that participates in RNA processing, alternative splicing, and chromosome maintenance. hnRNP A1 can be proteolyzed to unwinding protein (UP1), a 22.1-kDa protein that retains a high affinity for purine-rich single-stranded nucleic acids, including the human telomeric repeat (hTR) d(T-TAGGG) n . Using the structure of UP1 bound to hTR as a guide, we have incorporated the fluorescent guanine analog 6-MI at one of two positions within th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 48 publications
6
53
0
Order By: Relevance
“…This result is consistent with a previous study showing that UP1 can unfold a G-quadruplex formed by the G-rich strand of minisatellite repeats, d(GGCAG)n (Fukuda et al 2002). Shamoo and colleagues (Myers et al 2003) also reported that UP1 can reduce the T m of the human telomeric oligonucleotide d(TAGGGT) 4 in a 150 mM K + -containing solution, from 67.0°C to 36.1°C, consistent with a G-quadruplex-destabilizing activity of UP1. Although not proven, it seems likely that hnRNP A1 can also disrupt a G-G hairpin, as hnRNP A/B proteins are well known to have nucleic acid helix-destabilizing activity (Riva et al 1986).…”
Section: A Model For Hnrnp A1 Stimulation Of Telomerase Processivitysupporting
confidence: 82%
“…This result is consistent with a previous study showing that UP1 can unfold a G-quadruplex formed by the G-rich strand of minisatellite repeats, d(GGCAG)n (Fukuda et al 2002). Shamoo and colleagues (Myers et al 2003) also reported that UP1 can reduce the T m of the human telomeric oligonucleotide d(TAGGGT) 4 in a 150 mM K + -containing solution, from 67.0°C to 36.1°C, consistent with a G-quadruplex-destabilizing activity of UP1. Although not proven, it seems likely that hnRNP A1 can also disrupt a G-G hairpin, as hnRNP A/B proteins are well known to have nucleic acid helix-destabilizing activity (Riva et al 1986).…”
Section: A Model For Hnrnp A1 Stimulation Of Telomerase Processivitysupporting
confidence: 82%
“…All these structures have been refined in the P4 3 2 1 2 space group from an identical tetragonal crystal form (pdb accession codes 2UP1, 1PGZ, 1PO6 and 1U1K to 1U1R) (Ding et al 1999;Myers et al 2003;Myers and Shamoo 2004). These bound structures are almost indistinguishable with a calculated average pairwise r.m.s.d.…”
Section: Introductionmentioning
confidence: 59%
“…Thus, hnRNP A1 interacts with the SLII hairpin loop using a mode of recognition likely distinct from its established mode of binding single strand nucleic acids. 28,30,48 This observation suggests that hnRNP A1 can accommodate different RNA substrates using sequence and shape-specific recognition principles. The results obtained here are in good agreement with our previous study that showed UP1 binds the HIV-1 ESS3 hairpin loop as a highaffinity 1:1 complex; however, the sequence of the ESS3 apical loop (5'-GAUUAGU-3') more closely matches the hnRNP A1 "winner."…”
Section: Discussionmentioning
confidence: 99%